2015
DOI: 10.1007/s00125-015-3648-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of insulin degludec and insulin glargine on day-to-day fasting plasma glucose variability in individuals with type 1 diabetes: a multicentre, randomised, crossover study

Abstract: Aims/hypothesisWe compared the effects of insulin degludec (IDeg; Des(B30)LysB29(γ-Glu Nε-hexadecandioyl) human insulin) and insulin glargine (IGlar; A21Gly,B31Arg,B32Arg human insulin) on the day-to-day variability of fasting plasma glucose (FPG) levels in individuals with type 1 diabetes treated with basal-bolus insulin injections.MethodsThe effects of basal-bolus insulin therapy for 4 weeks with either IDeg or IGlar as the basal insulin in adult C-peptide-negative outpatients with type 1 diabetes were inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 19 publications
5
24
0
Order By: Relevance
“…The 2-year extension of the main BEGIN trial [22] indicated that the hypoglycemia-reducing benefits of IDeg were observed at night, rather than during the day; this is likely because a relationship exists between bolus insulin and diurnal hypoglycemia, whereas the ultra-long acting and less variable glucose-lowering effects of IDeg may better decrease nocturnal hypoglycemia. Some other studies [9,13,[17][18][19][23][24][25][26], including our recent study [14], also demonstrated a greater reduction in the risk of nocturnal hypoglycemia, rather than an overall decrease, with IDeg in all-aged patients with type 1 diabetes. The outcomes of an earlier 1-year study of IDeg in Japanese adults with type 2 diabetes were consistent with our observations [11].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The 2-year extension of the main BEGIN trial [22] indicated that the hypoglycemia-reducing benefits of IDeg were observed at night, rather than during the day; this is likely because a relationship exists between bolus insulin and diurnal hypoglycemia, whereas the ultra-long acting and less variable glucose-lowering effects of IDeg may better decrease nocturnal hypoglycemia. Some other studies [9,13,[17][18][19][23][24][25][26], including our recent study [14], also demonstrated a greater reduction in the risk of nocturnal hypoglycemia, rather than an overall decrease, with IDeg in all-aged patients with type 1 diabetes. The outcomes of an earlier 1-year study of IDeg in Japanese adults with type 2 diabetes were consistent with our observations [11].…”
Section: Discussionsupporting
confidence: 56%
“…In the present study, the daily dose of IDeg was numerically decreased, but did not significantly differ during the 24-week study period relative to the baseline; therefore, the administration of a conservative dose is recommended in children of age<15 years with type 1 diabetes upon switching from IGlar previously given once daily to IDeg. Subsequently, this dose can be adjusted according to the patient's blood glucose levels to avoid occurrence of hypoglycemia [9,11,18,19,[24][25][26]. The dose-adjustment could affect a risk of hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…In recent Japanese reports, Kusunoki et al [27] demonstrated that PG levels during evening time tended to decrease after switching to IDeg from other Las as evaluated by CGM in patients with once-daily injection of La at baseline. Nakamura et al [28] showed that the mean and SD of FPG were significantly smaller at lower dose of insulin with IDeg than with IGlar in a multicenter, randomised, crossover study for adults with type 1 diabetes. On the other hand, Thalange et al [17] similarly reported that significant decrease of FPG with lower dose of insulin was observed with IDeg than with IDet in children and adolescents with type 1 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction rate was remarkable in patients receiving twice-daily injections of basal insulin (76.0% of the value at baseline) as compared with those given oncedaily injections (82.6% of the value at baseline) before IDeg use. Previous studies of adults with type 1 diabetes have recommended reducing the dose of IDeg by <10-20% for patients who previously received oncedaily injection of IGlar, and by 20-40% for those previously given twice-daily injections [14,25,[26][27][28]. By contrast, Yamada et al [29] reported that there was no need to reduce the dose of IDeg from those given initially in Japanese adults with type 1 diabetes.…”
Section: Author Disclosure Statementmentioning
confidence: 99%
“…In the last few years, a novel ultra-long-acting insulin has been developed (insulin degludec (IDeg) (®Tresiba/ Novo Nordisk, Bagsvaerd, Denmark)). A recent study has shown that intensive insulin therapy with IDeg is related to less frequent nocturnal hypoglycemic events (13), lower levels and smaller day-to-day variability of fasting plasma glucose (14) while implementing a lower daily insulin dose (15). It also showed a comparable symptomatic and cognitive response to artificially induced hypoglycemia (16) Copyright © 2017, Sports Medicine Research Center.…”
Section: Introductionmentioning
confidence: 99%